The final pagan generation - Watts, Edward Jay, 1975- (Oakland, California : University of California Press, 2015)
The Final Pagan Generation recounts the fascinating story of the lives and fortunes of the last Romans born before the Emperor Constantine converted to Christianity. Edward J. Watts traces their experiences of living through the fourth century's dramatic religious and political changes, when heated confrontations saw the Christian establishment legislate against pagan practices as mobs attacked pagan holy sites and temples. The emperors who issued these laws, the imperial officials charged with implementing them, and the Christian perpetrators of religious violence were almost exclusively youn.
Cover; Title; Copyright; Dedication; Contents; List of Illustrations; Acknowledgments; Introduction; 1. Growing Up in the Cities of the Gods; 2. Education in an Age of Imagination; 3. The System; 4. Moving Up in an Age of Uncertainty; 5. The Apogee; 6. The New Pannonian Order; 7. Christian Youth Culture in the 360s and 370s; 8. Bishops, Bureaucrats, and Aristocrats under Gratian, Valentinian II, and Theodosius; 9. Old Age in a Young Man's Empire; 10. A Generation's Legacy; Notes; Bibliography; Index
Description based upon print version of record.
Includes bibliographical references.
Keywords: Paganism -- Rome; Christianity and other religions -- Rome; Rome -- Religion; Christianity and other religions -- Rome; Paganism -- Rome; Rome -- Religion; RELIGION / Christian Church / History; RELIGION / Christianity / History; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Antiquities & Archaeology; Electronic books